THE CONTENT AND PROSPECTS OF THE GAME OF RUGBY - Jumaniyazov Maksudbek Karimovich (Western European Studies, 2024)
Currently, rugby is one of the rapidly developing sports in our country. The Rugby Federation of Uzbekistan and its regional divisions have been established and are functioning, the national rugby team of Uzbekistan actively participates in prestigious international competitions at the Asian Games and takes honorable places. among the top eight countries in the region. Further development of rugby, its active promotion and popularization among the broad sections of the population of the republic, provision of high-quality training process, creation of favorable conditions for continuous improvement of skill level and qualification of rugby players, trainers and referees , as well as the first resource in Uzbek language was prepared for athletes and coaches in order to train rugby players. As a result of the continuous support of the leadership of our government, great attention is also paid to the sport of Rugby
Keywords: Games; Asian; training; rugby